Achieving experiential accessibility in nature: accommodating persons with disabilities in trail design - Balderston, Allison (Kansas State University, 2016)
The absence of participation in physical activity is a public health concern for all people, but even more of a problem for the estimated 52 million Americans with disabilities (Rimmer 2005). Besides the physical health benefits derived from physical activity, when a trail leads through a natural setting, research shows that significant sensory and cognitive benefits can also be gained which leads to greater well-being (Maller et al. 2005; Hull and Michael 1995; Kaplan 1995; Irvine and Katherine 2002). Furthermore, when trails are planned and constructed in natural settings, most of the attention is directed at minimizing environmental impacts at the exclusion of maximizing the physical, sensory, and cognitive experience of users. This shortcoming is compounded when the user has disabilities. Besides typical disability concerns related to mobility, disabilities to be better accommodated in trail design also include vision and hearing impairments. The focus of this research is investigating how trail planning and design in natural settings can better provide for the physical, sensory, and cognitive experience of users, particularly those users who have disabilities. Findings informed the development of Natural Trail Design Guidelines prepared for the City of Manhattan Parks and Recreation Department who is seeking to improve the City’s existing natural trails. Sample designs for trail enhancements at Anneberg Park and the Konza Prairie near Manhattan, Kansas were proposed. Once implemented and assessed to be found successful, the Natural Trail Design Guidelines might be transferable to other locations.
Keywords: Trail design; Accessibility; Experience; Universal design